2020
DOI: 10.1021/acs.jpcb.0c05932
|View full text |Cite
|
Sign up to set email alerts
|

On the X-ray Scattering Pre-peak of Linear Mono-ols and the Related Microstructure from Computer Simulations

Abstract: The X-ray scattering intensities (I(k)) of linear alkanols OH­(CH2) n−1CH3 obtained from experiments (methanol to 1-undecanol) and computer simulations (methanol to 1-nonanol) of different force field models are comparatively studied particularly in order to explain the origin and the properties of the scattering pre-peak in the k-vector range 0.3–1 Å–1. The experimental I(k) values show two apparent features: the pre-peak position k P decreases with increasing n, and more intriguingly, the amplitude A P goes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 65 publications
3
65
1
Order By: Relevance
“…Typically the diffraction intensities of monohydroxy alcohols exhibit two prominent features, (i) a main peak reflecting the average particle-particle distance, which is dictated by the size of the methylene group for larger alcohols and (ii) a characteristic pre-peak at lower momentum transfer that is assigned to clusters of hydroxyl groups surrounded by their alkyl tails 40,41 . In a previous study of monohydroxy alcohols 39 , we showed that the intensity of the pre-peak is not directly related to the local cluster microstructure, while its position is correlated to the mean size of the formed meta-objects. Strictly speaking, this structure is reflected in the various atom-atom correlation functions and structure factors, but these are not directly experimentally observed and can only be obtained through computer simulations.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…Typically the diffraction intensities of monohydroxy alcohols exhibit two prominent features, (i) a main peak reflecting the average particle-particle distance, which is dictated by the size of the methylene group for larger alcohols and (ii) a characteristic pre-peak at lower momentum transfer that is assigned to clusters of hydroxyl groups surrounded by their alkyl tails 40,41 . In a previous study of monohydroxy alcohols 39 , we showed that the intensity of the pre-peak is not directly related to the local cluster microstructure, while its position is correlated to the mean size of the formed meta-objects. Strictly speaking, this structure is reflected in the various atom-atom correlation functions and structure factors, but these are not directly experimentally observed and can only be obtained through computer simulations.…”
Section: Introductionmentioning
confidence: 73%
“…For a detailed analysis, the intensity, FWHM (Full Width at Half Maximum) and position of both the pre-peak and the main peak were determined by a fit with a Pearson VII function and a linear slope in the corresponding peak area (see Ref. 39 for details). The corresponding error bars were determined by changing the fit ranges.…”
Section: Experiments and Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Such a feature and corresponding behaviour as a function of chain length are uncommon in simple organic liquids, which are usually homogeneous at mid-long scales, presenting flat SAXS patterns below 1 Å À1 . Nevertheless, the pre-peak has been reported in markedly amphiphilic systems such as n-alcohols, [27][28][29][30] and n-aldehydes, 31,32 and also in more complex systems like ionic liquids, [33][34][35][36] deep eutectic solvents, 37 and pseudo-ionic liquids. [38][39][40] The trend of the pre-peak position as a function of the alkyl tail length is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%